Imeglimin-based therapies improve glycemic control and reduce mitochondrial stress in type 2 diabetes: a prospective cohort study - Satheesan, Abhishek; Kumar, Janardanan Subramonia; Vajravelu, Leela Kakithakara; Murugesan, Ria (Frontiers in Endocrinology, 2025)
BackgroundImeglimin, a novel oral antidiabetic agent, has demonstrated mitochondrial and anti-inflammatory benefits. This study evaluated the efficacy of Imeglimin-based therapies on glycemic control, mitochondrial stress (circulating cell-free mitochondrial DNA (ccf-mtDNA), and inflammation in type 2 diabetes mellitus (T2DM).MethodsA total of 104 T2DM patients were enrolled and assigned to one of four groups out of which 96 patients completed follow-up and data was analyzed: Imeglimin monotherapy (n=23), Imeglimin + Metformin (n=24), Imeglimin + other Oral Hypoglycemic Agents (OHAs) (n=24), and Metformin + other OHAs (n=25). Assessments at baseline and 6 months included HbA1c, lipid profile, ccf-mtDNA, NOD-like receptor family, pyrin domain containing 3 (NLRP3), Interleukins-6, 1β and 18 (IL-6, IL-1β, and IL-18). Within-group changes were assessed using paired t-tests. Repeated measures ANCOVA models analyzed group-time interactions. Correlation analysis explored associations between Δ biomarkers and metabolic parameters.ResultsCombination therapies, particularly Imeglimin + other OHAs, significantly reduced HbA1c (Δ=–0.5%, p=0.001), ccf-mtDNA (Δ=–18.5 copies/μL, p=0.02), and IL-6 (p< 0.001). Repeated measures ANCOVA revealed significant reductions in HbA1c (p=0.001), circulating cell-free mtDNA (p=0.004), and serum NLRP3 levels (p=0.037) across imeglimin-based therapy groups. Post hoc comparisons showed the greatest improvements in the Imeglimin + Other OHAs group versus control. Significant time × group effects for IL-6 and IL-1β. No changes were noted in IL-18.ConclusionImeglimin, especially in combination with non-Metformin OHAs, improves glycemic control and reduces mitochondrial and inflammatory stress in T2DM patients. These findings support its use as an adjunctive therapy with broader metabolic benefits.Clinical Trial Registrationhttps://ctri.nic.in/Clinicaltrials/advancesearchmain.php, identifier CTRI/2023/12/060844.